Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/slct.201700043
|View full text |Cite
|
Sign up to set email alerts
|

A DFT Exploration of Efficient Catalysts Based on Metal‐Salen Monomers for the Cycloaddition Reaction of CO2 to Propylene Oxide

Abstract: Using quantum chemistry calculations, we explored the interactions between non‐rare earth metal‐salophen complex (M‐Salen) monomers and propylene oxide (PO) and explored the catalytic mechanisms for the cycloaddition reaction of CO2 to epoxides by the M‐Salen monomers. Our theoretical results demonstrated that a larger binding energy for M‐Salen interacting with PO results in a lower apparent barrier height for the cycloaddition reaction. The CrIII‐Salen monomer possessed the lowest apparent barrier, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 44 publications
2
6
0
Order By: Relevance
“…It was also shown that Mn III salen complexes are not detrimental to the epoxide yield in these conditions while Cr III -salophen-CO 2 H leads to more epoxide ring opening as the result of its higher Lewis acidity compared to Mn III . The ability of Cr III -salophen-CO 2 H to activate epoxides 33 and our previous results on the cycloaddition of CO 2 onto styrene oxide using Cr III -salophen-CO 2 H (ref.…”
Section: One-pot Oxidative Carboxylation Of Styrene Using Co 2 and Osupporting
confidence: 61%
“…It was also shown that Mn III salen complexes are not detrimental to the epoxide yield in these conditions while Cr III -salophen-CO 2 H leads to more epoxide ring opening as the result of its higher Lewis acidity compared to Mn III . The ability of Cr III -salophen-CO 2 H to activate epoxides 33 and our previous results on the cycloaddition of CO 2 onto styrene oxide using Cr III -salophen-CO 2 H (ref.…”
Section: One-pot Oxidative Carboxylation Of Styrene Using Co 2 and Osupporting
confidence: 61%
“…The Co­(III)­K­(I) catalyst is a rare example of a dinuclear complex active using propylene oxide/carbon dioxide and operating without any cocatalyst. Regardless of the catalyst structure, there are very few other investigations into the PO/CO 2 ROCOP mechanism, the majority of studies apply DFT calculations to investigate specific steps such as epoxide binding, CO 2 insertion, chain dissociation, or backbiting reactions, independent of the complete cycle. One rationale for these “simplified” investigations is that the presence of the cocatalyst complicates the active site speciation.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that no styrene oxide conversion was observed with these two last cocatalysts at 50 °C. This should be seen in conjunction with the DFT calculations performed by Deng and Lu's team, which concern the interactions between different metal-salophen complex monomers and propylene oxide (Wu et al, 2017). Of all the metals tested, Cr(III) was indeed found to have the highest binding energy with propylene oxide (15.4 kcal mol −1 ), higher than those of Mn(III) and Ni(II), although not higher than the desorption energy of the products.…”
Section: Synthesis and Characterization Of The Co-catalystsmentioning
confidence: 83%